Badly Behaved Detrital (U‐Th)/He Ages: Problems With He Diffusion Models or Geological Models?. (25th May 2019) - Fox, Matthew; Dai, Jin‐Gen; Carter, Andrew
Abstract: Dispersion in apatite (U‐Th)/He ages makes extracting thermochronological information challenging. This is particularly problematic for constraining the thermal history of sedimentary basins, as the total amount of heating during burial can be small and at the limits of the sensitivity of the apatite (U‐Th)/He system in apatite, but undetectable with other thermochronometric systems. Here we explore the importance of the differences in predepositional thermal histories for individual crystals and the effect of radiation damage‐related diffusion during both the predepositional and postdepositional thermal history on the dispersion of apatite (U‐Th)/He ages. Different predepositional thermal histories can lead to a large spread of detrital ages due to radiation damage and its effect on He diffusivity. The resulting ages may appear scattered, and relationships between age and [eU], a conventional proxy for accumulated radiation damage, may be nonexistent or nonsensical. Furthermore, other variables that are expected to control He diffusivity could vary as a function of source region, resulting in false conclusions about controls on He diffusivity and the applicability of the apatite (U‐Th)/He system in general. We suggest that in some situations in which detrital apatite (U‐Th)/He age does not correlate with [eU], it is not because of problems with the thermochronometric system, but problems with the assumed geological model. Key Points: A radiation damage control on detrital apatite (U‐Th)/He ages does not require positive correlations between age and effective uranium Effective uranium is a proxy for radiation damage, but interpretations must account for the complete thermal history Not accounting for prior history increases the potential to incorrectly attribute diffusivity variations on chemical compositions